Comparison of venom composition and biological activities of the subspecies Crotalus lepidus lepidus, Crotalus lepidus klauberi and Crotalus lepidus morulus from Mexico - Martínez Romero, Gerardo (2013)
The rock rattlesnakes Crotalus lepidus comprise a group (lepidus, klauberi, morulus and maculosus) of poorly known mountain cold-tolerant snakes in Mexico. In particular, Crotalus lepidus morulus is a snake endemic of the northeast of Mexico, whereas Crotalus lepidus klauberi and C. l. lepidus are distributed in some regions of the north and central Mexico and southern U. S. Until now very little data are available from C. lepidus subspecies from Mexico, as the terrain inhabited by these snakes is generally steep and rugged. In this work, we have determined some biochemical and biological properties of C. l. morulus, C. l. klauberi and C. l. lepidus crude venoms. Some minor differences in venoms were noted in SDS-PAGE, HPLC profile and MALDI-TOF mass spectrometry analysis. Partial sequences of metalloproteinases, phospholipases A2 (PLA2) and galactose-specific lectins were identified in the venoms. Venoms of C. l. klauberi and C. l. lepidus had significantly higher hemorrhagic and lethal activities than C. l. morulus venom. Proteolytic activity in azocasein was higher in C. l. morulus venom, whereas gelatin hydrolysis was higher in C. l. klauberi. Fibrinogenolytic and PLA2 activities were very similar in all venoms tested. The histological observations in the gastrocnemius muscle damaged by venoms from all the subspecies confirmed myonecrotic and hemorrhagic activities (at 3 and 24 h), which resulted in a poor regenerative response after 14 days. However, C. l. lepidus and C. l. klauberi venom induced a higher increase in the plasma activity of creatine kinase (CK), evidencing higher myotoxicity, whereas paw edema-inducing activity was higher in C. l. lepidus venom. The results indicate that the venoms from the three subspecies have similar protein profiles in electrophoresis, HPLC and molecular weight determinations. However, differences were found in the biological activities in mice. Notably, the venoms of C. l. lepidus and C. l. klauberi present higher toxicity (lower LD50) and hemorrhagic activity than C. l. morulus venom.